Manufacturing and Application of Stainless Steels - Di Schino, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Stainless steels represent a quite interesting material family, both from a scientific and commercial point of view, following to their excellent combination in terms of strength and ductility together with corrosion resistance. Thanks to such properties, stainless steels have been indispensable for the technological progress during the last century and their annual consumption increased faster than other materials. They find application in all these fields requiring good corrosion resistance together with ability to be worked into complex geometries. Despite to their diffusion as a consolidated materials, many research fields are active regarding the possibility to increase stainless steels mechanical properties and corrosion resistance by grain refinement or by alloying by interstitial elements. At the same time innovations are coming from the manufacturing process of such a family of materials, also including the possibility to manufacture them starting from metals powder for 3D printing. The Special Issue scope embraces interdisciplinary work covering physical metallurgy and processes, reporting about experimental and theoretical progress concerning microstructural evolution during processing, microstructure-properties relations, applications including automotive, energy and structural.